1986
DOI: 10.1111/j.1365-2923.1986.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles and approaches: implications for medical education

Abstract: This paper reviews the recent literature on learning styles and approaches to learning. It identifies two separate streams of research, one originating from mainstream cognitive and psychometric psychology and one from research undertaken within the everyday learning environment. The latter is dealt with in greater detail as it seems to have more immediate practical relevance. A simple model of the teaching-learning process is presented showing how students learn in different ways which are partly attributable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
383
2
30

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(428 citation statements)
references
References 21 publications
13
383
2
30
Order By: Relevance
“…Subsequent research identified a third approach, namely the strategic approach which is associated with competitive students whose predominant motivation is the achievement of good grades. Their intention is to outperform others (Entwistle 1988a(Entwistle , 1988bEntwistle et al 2000;Tait et al 1998) and to achieve their aim they adopt a deep or a surface approach, depending on which is likely to produce the most successful results (Newble and Entwistle 1986). In this regard, research suggests that business students exhibiting strategic learning characteristics are more likely to achieve their goal of good grades by adopting an approach based on a desire to understand (deep) rather than one of rote memorization (surface) (Rodriquez 2009).…”
Section: Business Ethics and Students' Approaches To Learningmentioning
confidence: 99%
“…Subsequent research identified a third approach, namely the strategic approach which is associated with competitive students whose predominant motivation is the achievement of good grades. Their intention is to outperform others (Entwistle 1988a(Entwistle , 1988bEntwistle et al 2000;Tait et al 1998) and to achieve their aim they adopt a deep or a surface approach, depending on which is likely to produce the most successful results (Newble and Entwistle 1986). In this regard, research suggests that business students exhibiting strategic learning characteristics are more likely to achieve their goal of good grades by adopting an approach based on a desire to understand (deep) rather than one of rote memorization (surface) (Rodriquez 2009).…”
Section: Business Ethics and Students' Approaches To Learningmentioning
confidence: 99%
“…Estas variables han sido objeto de estudio, durante las últimas décadas, por parte de escuelas de medicina europeas y norteamericanas por su posible relación con el desempeño académico, la elección de especialidad y la satisfacción de sus alumnos [1][2][3][4][5][6][7][8] . En Chile se ha investigado la relación entre rasgos psicopatológicos y rendimiento académico en estudiantes universitarios 9,10 , pero no hay estudios que relacionen características de personalidad de individuos clínicamente normales y desempeño académico.…”
unclassified
“…Consistent with the educational principles of patientcentered and problem-oriented learning, basic science concepts are presented within a clinical context. Problem based learning produces deep levels of learning and understanding and an ability to apply basic science knowledge in the clinical setting (Newble & Entwhistle, 1986;Norman & Schmidt, 1996). Since assessment influences the approach to learning (Newble & Entwhistle, 1986), the UPT aims at reinforcing this learning style by linking the basic science questions to the clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…Problem based learning produces deep levels of learning and understanding and an ability to apply basic science knowledge in the clinical setting (Newble & Entwhistle, 1986;Norman & Schmidt, 1996). Since assessment influences the approach to learning (Newble & Entwhistle, 1986), the UPT aims at reinforcing this learning style by linking the basic science questions to the clinical cases. The cases provide a real-life context for clinical reasoning and should lead to external face validity of the test.…”
Section: Introductionmentioning
confidence: 99%